1966
DOI: 10.1128/am.14.4.497-505.1966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Filters for Removal of Bacteriophages from Air

Abstract: Glass wool, nonabsorbent cotton, fiberglass filter medium, and a commercial absolute filter were tested for effectiveness in removing aerosolized bacterial viruses under low flow rate (1 ft 3 /min) and high flow rate (10 to 25 ft 3 /min) air-flow conditions. Special equipment was designed for measurement of filter efficiencies under the two air-flow conditions. Under low air-flow rate test conditions, glass wool was only 98.543 to 99.83% efficient, whereas cotton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Five of seven aerosolized virus studies found that filtration was associated with virus removal using PRRSV [ 30 ], equine arteritis virus (EAV) [ 30 ], bovine enterovirus (BEV) [ 30 ], human adenovirus [ 29 ], and the bacteriophages T7 [ 27 , 28 ] and MS2 [ 31 ]. One study found that increasing MERV rating was associated with decreasing virus concentration for bacteriophage T4 at different locations within an apartment unit [ 40 ], and another found that increasing MERV rating was associated with increasing viral filtration efficiency using bacteriophage MS2 in a test duct set-up [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five of seven aerosolized virus studies found that filtration was associated with virus removal using PRRSV [ 30 ], equine arteritis virus (EAV) [ 30 ], bovine enterovirus (BEV) [ 30 ], human adenovirus [ 29 ], and the bacteriophages T7 [ 27 , 28 ] and MS2 [ 31 ]. One study found that increasing MERV rating was associated with decreasing virus concentration for bacteriophage T4 at different locations within an apartment unit [ 40 ], and another found that increasing MERV rating was associated with increasing viral filtration efficiency using bacteriophage MS2 in a test duct set-up [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al noted that the filter efficiency associated with E 1 (i.e., 0.30–1.0 μm; the smallest particle size range for MERV classification) was a good approximation of the viral filtration efficiency [ 26 ]. In addition, prior to the use of MERV ratings as developed in 1999, Washam et al identified cost differences between filters of similar efficiency [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations